2015
DOI: 10.3892/mmr.2015.3589
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of chemokine receptor 4 inhibition by AMD3100 in biliary tract cancer cells: Potential drug synergism with gemcitabine

Abstract: Abstract. Biliary tract cancer (BTC) remains one of the most life-threatening types of cancer due to the lack of efficient therapies. Advanced tumour stages at the point of diagnosis and high chemoresistance are two of the predominant reasons for a 5-year survival rate of only ~5%. The present study investigated the effect of the chemokine receptor 4 (CXCR4) inhibitor AMD3100 (Plerixafor), alone and in combination with standard gemcitabine chemotherapy, on the proliferation of BTC cells. The expression of CXCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Drug-based inhibition of CXCR4 using AMD3100 suppressed migration and invasion of BTC cells, and this effect was only observable in the CD24+ CSC subpopulation[50]. Interestingly, AMD3100 treatment also reduced sphere formation potential of BTC cells in another study, further connecting CXCR4 expression with stem cell characteristics[51]. RNA interference-mediated knockdown of CXCR4 in an IHC model inhibited proliferation and colony formation in vitro as well as tumorigenicity in vivo [52].…”
Section: Cancer Stem Cell Markers In Biliary Tract Cancer - An Overviewmentioning
confidence: 99%
“…Drug-based inhibition of CXCR4 using AMD3100 suppressed migration and invasion of BTC cells, and this effect was only observable in the CD24+ CSC subpopulation[50]. Interestingly, AMD3100 treatment also reduced sphere formation potential of BTC cells in another study, further connecting CXCR4 expression with stem cell characteristics[51]. RNA interference-mediated knockdown of CXCR4 in an IHC model inhibited proliferation and colony formation in vitro as well as tumorigenicity in vivo [52].…”
Section: Cancer Stem Cell Markers In Biliary Tract Cancer - An Overviewmentioning
confidence: 99%
“…Inhibition of the signaling pathway with CXCR4 antagonists decreases the motility and invasion of CCA cells 15 - 17 . Inhibition of CXCR4 can also reverse drug resistance and improve chemotherapy 18 , 19 , as documented by the chemosensitizing effect of a CXCR4 antagonist AMD3100 to GEM in human CCA cells 20 . Several studies reported that CXCR4 inhibition reduced the stemness of cancer cells to overcome drug resistance 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%